Yahoo Web Search

  1. k =1 , 3/2 k =2 , 5/8 k =3 , 10/26 the serie convergens to the asymptote 2^ k / 3^ k = (2/3)^ k and for k -->oo , (2/3)^ k =0 couse for every n , |n|<1 it will be convergens to 0

    2 Answers · Science & Mathematics · 28/03/2011

  2. " k multiplied by three": 3k "the sum of k multiplied by three and k ": 3k + k "the sum of k multiplied by three and k is 12": 3k + k = 12 3k + k = 12 4k = 12 k = 12/4 k = 3

    2 Answers · Science & Mathematics · 22/04/2012

  3. Since k is a natural number, then it's either even or odd. If k ...then we can let k = 2m for some other natural number "m". Then k ( k +1) = 2 * m( k +1), so 2 clearly divides it. If k is odd...

    1 Answers · Science & Mathematics · 21/02/2011

  4. k = 9 Note that: z^2 - 6x + 9 = (z - 3)^2, so it is a perfect square To find k , just divide b = -6 by 2, and then square it. Hope that helps.

    2 Answers · Science & Mathematics · 19/12/2008

  5. k ^x = e^xln( k ) and has no Fourier transform k ^-x = e^-xln( k ) has the transform (√(2/π))[(ln( k ))/(((ln( k ))^2 + ω^2)] , k > 1, x > 0

    2 Answers · Science & Mathematics · 15/08/2007

  6. k * (220)^x = 0.044 or (220)^x = 0.044 / k convert to logarithmic formula x = log_220( 0.044 / k ) convert to base 10 log x = log_10( 0.044 / k ) / log_10(220) or x = log_10( 0.044 / k ) / 2.34 hence x = (1/2.34)log_10( 0.044 / k )

    3 Answers · Science & Mathematics · 02/05/2013

  7. C(p, k ) = p! / k ! (p- k )!. So C(p, k ) k ! (p- k )! = p!. Consider the unique factorization in prime numbers of C(p, k ) k ! (p- k )! = p!. The prime factors of C(p, k ) k ! (p- k ...

    4 Answers · Science & Mathematics · 18/09/2007

  8. K ^2[1 + (dy/dx)^2] = (dy/dx)^2 (dy/dx)^2 ( K ^2 - 1) = - K ^2 dy/dx = K /√(1- K ^2) thus y = Kx/√(1- K ^2) + C

    2 Answers · Science & Mathematics · 04/09/2009

  9. k ^2 + 9k + 14 > 0 ( k + 2)( k + 7) > 0 k > -2 or k < -7 in the interval notation : (-∞, -7) U (-2, ∞)

    2 Answers · Education & Reference · 11/10/2013

  10. k /3 = 8 - k multiply each side by 3 k = 3(8 - k ) k = 24 -3k 4k = 24 k = 6

    8 Answers · Science & Mathematics · 01/11/2011

  1. Try asking your question on Yahoo Answers